Analysis of vibration in cam follower system - Mohd Hanaffi, Othman (2009)
Cam is a mechanical component that translates movement from circular to reciprocating by using mating component, called the follower. The principal aim of this work is to study and analysis the vibration factor on vertical position cam using heart shape cam. Then, verifies the data using DYNACAM simulated and analysis the effect of impact force on vibration in cam follower system. The parameters such as displacement, velocity and acceleration are involved in finding the optimum force to the system of vibration cam in high speed rotation per minute (RPM). The analysis process will be done using DYNACAM simulation software that able to verify the results from obtained the experiment whether the data are correct or not for principal of vibration in cam follower system. The analysis process also focus on the jump force of follower, that effect of vibration factor in cam mechanism system. During analysis data will be process, high speed will be select from the types of speed of cam in follower system. The speeds that will be used are 300RPM and it is suitable for analyze the vibration factor and more accurate. When high speeds system pumping chemically processed air can have gradually applied loads.